Pengaruh Pemberian Berbagai Konsentrasi Timbal (Pb) terhadap Pertumbuhan Bibit Mangrove Rhizophora stylosa - Sucika Armiani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
Mangroves are a type of higher plant found in coastal areas that play many roles, one of which is as a bioaccumulator of harmful pollutants. One such harmful pollutant is the heavy metal Lead (Pb). This study aims to determine the effect of various concentrations of lead on the growth of mangrove seedlings, specifically Rhizophora stylosa. This research is an experimental study using a Completely Randomized Design (CRD). There were four lead concentration treatments: K0 = 0 ppm (control); K1 = 0.1 ppm; K2 = 1 ppm; K3 = 10 ppm; and K4 = 100 ppm. Each treatment was repeated five times, resulting in 25 experimental units. The seedlings used were Rhizophora stylosa, approximately 8 months old, with an average height of 70 cm and an average of 8 leaves. The growing medium used was homogenized mud soil. Before the experiment, the plants were acclimatized for 1 week. The treatment involved a solution of Pb acetate administered every day for 6 weeks. The parameters measured included plant height increase (cm), leaf area (cm²), increase in the number of leaves, increase in the number of shoots, and increase in stem diameter (cm). Based on observations over the 6-week treatment period, the average stem growth was between 0.12-0.28 cm, with no increase in stem diameter, an average leaf area increase of 0.14-0.38 cm², an increase in shoots by 1-3, and an increase in the number of leaves by 2-6. The ANOVA results at a significance level of 5% indicated that lead concentrations of 0-100 ppm did not significantly affect the growth of Rhizophora stylosa seedlings.